2020
DOI: 10.1111/jfpp.14736
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of jamun pomace as functional ingredients to enhance the physico‐chemical and sensory characteristics of ice cream

Abstract: Jamun (Syzygium cumini L.) is a tropical fruit crop that belongs to the Myrtaceae family (Singh, Paswan, & Rai, 2019).). India and Indonesia are viewed as the origin of jamun fruits. Jamun has recently become famous for its high nutritional value in food processing areas. Jamun provides ellagic acid and glucoside jamboline that reduces blood sugar and has excellent diabetes control; it is very effective to treat jaundice, kidney stone, blood pressure, sore throat, constipation, vomiting, and diarrhea. As a sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 27 publications
3
13
0
Order By: Relevance
“…Similar results were reported by Shelke et al. (2020) on ice cream containing jamun peel fiber (1–4%). However, Crizel et al.…”
Section: Application Of Dietary Fibers In Ice Creamssupporting
confidence: 90%
See 3 more Smart Citations
“…Similar results were reported by Shelke et al. (2020) on ice cream containing jamun peel fiber (1–4%). However, Crizel et al.…”
Section: Application Of Dietary Fibers In Ice Creamssupporting
confidence: 90%
“…Akalın et al ( 2018) also indicated the textural benefits of different DF (2%), with orange, apple, and wheat fibers providing better hardness and texture properties. Similar improvement in ice cream hardness has been observed by the addition of orange fiber (1.5%) (Crizel et al, 2014), jamun fruit pomace (4%) (Shelke et al, 2020), and corn fiber (2%) (Ayar et al, 2018). However, some studies have reported the adverse effects of DF (orange peel and pitaya) on texture and overall acceptability (Crizel et al, 2013;Utpott et al, 2020).…”
Section: Texturementioning
confidence: 62%
See 2 more Smart Citations
“…Moreover, the best sensory attributes were obtained when ice cream was treated with 3% of S. cumini pomace [146]. Another study conducted by Talukder et al (2020) [147] made use of the unique feature of anthocyanins (change in color with the change in pH) and applied S. cumini anthocyanins as a quality indicator for meat products.…”
Section: Value-added Food Products and Food Packaging Materialsmentioning
confidence: 99%